Virtual Discussion for EFL Students Establishing Three Domains: Cognitive, Affective, and Psychomotor - Sari, Ike Dian Puspita; Rahmah, Tities Hijratur (Universitas Malikussaleh, 2019)
In teaching and learning process, teacher may use certain learning strategies or methods. Virtual discussion, for instance, it can be done to encourage students cognitive, affective, and psychomotor. This activity provides an opportunity for students to sit and listen as they speak and think critically, logically, and rationally. Moreover, students get better results when they work together than those who study individually. This survey research conducted to find out the correlation among virtual discussion with cognitive, affective, and psychomotor of 110 students in IKIP Budi Utomo Malang. The result shows that the virtual discussion has strong correlation not only in cognitive domain, but also it has strong correlation with affective and psychomotor domain. Almost all significant values are positive. There is only one negative significant value between cognitive and affective. Thus, it illustrates that the increasing of cognitive domain by applying virtual discussion is not always followed by the increasing of affective domain.